Análisis del control de inventarios de la Ferretería Villacrés - Veloz Paredes, Rubén Patricio (2021)
The present case study developed has allowed us to know in detail the problems faced by the “Ferretería Villacrés” due to the lack of an inventory control system. The correct administration of the inventories is fundamental in every company, and this is precisely the main weakness of the microenterprise studied; This affects the profitability caused by losses of the products, whether due to deterioration or expiration of the same. A point that cannot be ignored is the inventory rotation, with this it is known which are the products with the highest demand and which products are occupying space on the hanger or warehouse, generating losses in the same way, since that space can use for a higher turnover product. The inventory control system is a strategy used by the companies that lead the market, they have the most demanded products in their stock. One of the factors that negatively affect the inventory control system of the microenterprise is billing, from the study carried out it is known that sometimes invoices are filled out incorrectly and on other occasions invoices are not delivered to customers . In the development of the present case, it refers to the importance of inventories in the operation and efficiency of the company; These must be valued appropriately, thus knowing the actual amount of inventories that one owns. The most used method for the control and management of inventories is the use of the Kárdex Card, which facilitates the control of the movements of the products, recording their income, expenses and existing balances.